Sustainable Fire-Resistant Materials: Recycled Polyethylene Composites with Non-Halogenated Intumescent Flame Retardants for Construction Applications - Oluwatobi Elijah Akindele; Erick Gabriel Ribeiro dos Anjos; Antonio Benjamim Mapossa; Uttandaraman Sundararaj (Recycling)
This study explores the development of sustainable fire-resistant composites using a blend of recycled linear low-density polyethylene (rLLDPE) and low-density polyethylene (rLDPE) for construction applications. The incorporation of non-halogenated intumescent flame retardants (IFRs), specifically ammonium polyphosphate (APP) and melamine polyphosphate (MPP), was shown to enhance the flame retardance, thermal stability, and mechanical performance of these recycled polymer blends. IFRs were introduced at 5 wt.% and 10 wt.% concentrations, and their effects were evaluated using limiting oxygen index (LOI) testing and thermogravimetric analysis (TGA). Results showed that 10 wt.% APP and a combination of 5 wt.% APP with 5 wt.% MPP increased LOI values from 18.5% (neat polymer blend) to 21.2% and 22.4%, respectively, demonstrating improved fire resistance. Enhanced char formation, facilitated by IFRs, contributes to superior thermal stability and fire protection. TGA results confirmed higher char yields, with the rLLDPE/rLDPE/MPP5/APP5 composition exhibiting the highest residue (3.00%), indicating a synergistic effect between APP and MPP. Rheological and mechanical analysis showed that APP had more impact on viscoelastic behavior, while the combination of IFRs provided balanced mechanical properties despite a slight reduction in tensile strength. This research highlights the potential of recycled polyethylene composites in promoting circular economy principles by developing sustainable, fire-resistant materials for the construction industry, reducing plastic waste, and enhancing the safety of recycled polymer-based applications.